Development of an index to define overall disease severity in IBD. Issue 2 (25th October 2016) - Siegel, Corey A; Whitman, Cynthia B; Spiegel, Brennan M R; Feagan, Brian; Sands, Bruce; Loftus, Edward V; Panaccione, Remo; D'Haens, Geert; Bernstein, Charles N; Gearry, Richard; Ng, Siew C; Mantzaris, Gerassimos J; et al.
Abstract : Background and aim: Disease activity for Crohn's disease (CD) and UC is typically defined based on symptoms at a moment in time, and ignores the long-term burden of disease. The aims of this study were to select the attributes determining overall disease severity, to rank the importance of and to score these individual attributes for both CD and UC. Methods: Using a modified Delphi panel, 14 members of the International Organization for the Study of Inflammatory Bowel Diseases (IOIBD) selected the most important attributes related to IBD. Eighteen IOIBD members then completed a statistical exercise (conjoint analysis) to create a relative ranking of these attributes. Adjusted utilities were developed by creating proportions for each level within an attribute. Results: For CD, 15.8% of overall disease severity was attributed to the presence of mucosal lesions, 10.9% to history of a fistula, 9.7% to history of abscess and 7.4% to history of intestinal resection. For UC, 18.1% of overall disease severity was attributed to mucosal lesions, followed by 14.0% for impact on daily activities, 11.2% C reactive protein and 10.1% for prior experience with biologics. Overall disease severity indices were created on a 100-point scale by applying each attribute's average importance to the adjusted utilities. Conclusions: Based on specialist opinion, overall CD severity was associated more with intestinal damage, in contrast to overall UC disease severity, which was more dependent on symptoms and impact on daily life. Once validated, disease severity indices may provide a useful tool for consistent assessment of overall disease severity in patients with IBD.